Development of Model for Technoprenuership for Students at Universitas Sumatera Utara - Chaidir, Andreasen Proicnius; Nazaruddin; Pujangkoro, Sugiharto (TALENTA Publisher, 2022)
The number of entrepreneurs who are expected to become innovative industries in Indonesia only reached 0.24% of Indonesia's total population. College plays an important role in motivating young graduates to become technopreneurship. The number of innovations that arise compared to innovative product innovations is still very minimum every year. The main problem faced by students is that 52.15% of students don’t continue their innovation products because they don’t get funding 13.50% of students don’t continue their innovation products because they don’t know what to do, do, and don't get technical guidance, 11.66% of students want to graduate on time, 10.44% don’t get mentors/coaches who know how to develop and guide students well, 6.75% of students that there is no incubation platform, 5.5% of students do not dare to take the risk to enter the technopreneur world. Researchers then designed a dynamic model of technopreneur incubation and simulated a design model that aims to see how far the model can help innovative products get funding. The simulation was conducted with three scenarios. The result was 17.6% increase when the incubation program was extended, an increase of 27.46% when there was an improvement in infrastructure and 21.47% when mentor capacity was lowered.